An Analysis of Writing Problems in Descriptive Texts Faced by Third-Semester Students in the English Education Study Program at PSDKU Aru, Pattimura University - Laelaem, Ferdinan; Lekatompessy, Felicia Miranda (MATAI: International Journal of Language Education, 2024)
The purpose of this study was to identify students' challenges in writing descriptive texts in English. The research design employed in this study was a qualitative method. The population consisted of nine third-semester students from the English Education program at Pattimura University, PSDKU Aru. The instruments used in this study were a writing test and interviews. For data analysis, the study utilized the formula from Annasudjono (2010): F/N×100%, while qualitative data analysis followed the framework of Miles, Huberman, and Saldana (2014), including data reduction, data display, and conclusion drawing/verification. The results revealed that students faced significant challenges in writing descriptive texts in English, particularly in the areas of organization, mechanics, vocabulary, and language use. The study concluded that the researcher identified recurring problems in writing descriptive texts through the use of writing tests and interviews. These challenges were most evident in the aspects of content, organization, mechanics, vocabulary, and language use.